The Use of Statins in Hematopoietic Stem Cell Transplantation - Shimabukuro-Vornhagen, Alexander; Glossmann, Jan; Liebig, Tanja; Scheid, Christof; Bergwelt-Baildon, Michael v. (Current Stem Cell Research & Therapy, 2009)
Hematopoietic stem cell transplantation has become an established treatment for some patients with malignant and non-malignant hematologic diseases. More wide-spread use of this treatment modality is limited by its severe side effects. Graft-versus-host disease is a major cause of morbidity and mortality following allogeneic stem transplantation. Recent data from experimental research in murine models of GVHD and early stage clinical studies demonstrate the potential of statins in the prevention and treatment of acute and chronic GVHD. Statins are lipid lowering drugs, which reduce cholesterol production by inhibiting HMG-CoA reductase, the rate limiting enzyme of the mevalonate pathway. They are an already approved drug class with a well known toxicity profile. Besides lowering of cholesterol levels other pleiotropic effects contribute to the therapeutic activity of statins. Statins have immunomodulatory effects and inhibit a broad range of immune cells that play a role in the pathogenesis of GVHD, including antigen-presenting cells. In addition to preventing GVHD statins possess several other effects that might prove beneficial in the setting of allogeneic transplantation, such as cardiovascular protection and anti-neoplastic activity. Here we review the current knowledge on the use and effects of statins in patients who undergo allogeneic hematopoietic stem cell transplantation with a special focus on prevention and treatment of GVHD.